Effect of Composite Composition on Mechanical Properties of Banana Fiber Composites with Epoxy Matrix for Functional Materials - Yoga Ahdiat Fakhrudi; Kholis Nur Faidzin; rahayu mekar bisono (International Journal of Science, Engineering, and Information Technology, 2022)
Technological developments and the influence of globalization have an impact on increasing the need for the amount of material for industry. The many disadvantages of metal materials due to their large mass, difficult manufacturing processes, corrosive properties, and high production costs have resulted in reduced use of metal materials in various products. Nowadays, there are many replacement materials with mechanical properties that can resemble metal materials such as composites. The role of composites is very important in the development of today's industrial world. This study wanted to determine the effect of the composite composition of rias banana fiber and teak sawdust with epoxy resin on the mechanical properties of the composite. The results showed that the comparison of the composition of the composite using rias banana fiber and teak sawdust with an epoxy matrix had an effect on the mechanical properties. Increasing the percentage of resin composition increases the value of the surface hardness of the composite. The highest level of Rockwell hardness with a value of 117 HRB in sample D and the lowest 109 HRB in sample A. While the highest max strength value was produced by sample C with a composition of teak sawdust: rias banana fiber: epoxy is 20% : 40% : 40 %. The conclusion of this research is the more resin composition will increase the composite hardness test value.